Measurement in marketing - Malhotra, Naresh K.; Baumgartner, Hans; Weijters, Bert (Review of marketing research ;, 2022)
Measurement is at the core of empirical research in marketing because researchers need measures that faithfully represent the constructs in their theories. This 19th volume of Review of Marketing Research addresses important measurement issues to deepen readers' appreciation of the fundamental role of measurement in empirical research in marketing. Measurement in Marketing features a range of chapters from experts in the field who discuss the philosophical foundations of measurement, provide practical recommendations about measurement error and explore the latest research, offering guidance on the selection of appropriate implicit measures for capturing automatic cognitive processes. Measurement in Marketing is built to provide a state-of-the-art discussion of current topics in measurement and deepen readers' appreciation of the fundamental role of measurement in empirical research in marketing.